Structure and origin of Tuvan gene pool according to autosome SNP and Y-chromosome haplogroups - V. A. Stepanov; N. A. Kolesnikov; L. V. Valikhova; A. A. Zarubin; I. Yu. Khitrinskaya; V. N. Kharkov (Вавиловский журнал генетики и селекции)
Tuvans are one of the most compactly living peoples of Southern Siberia, settled mainly in the territory of Tuva. The gene pool of the Tuvans is quite isolated, due to endogamy and a very low frequency of interethnic marriages. The structure of the gene pool of the Tuvans and other Siberian populations was studied using a genomewide panel of autosomal single nucleotide polymorphic markers and Y-chromosome markers. The results of the analysis of the frequencies of autosomal SNPs by various methods, the similarities in the composition of the Y-chromosome haplogroups and YSTR haplotypes show that the gene pool of the Tuvans is very heterogeneous in terms of the composition of genetic components. It includes the ancient autochthonous Yeniseian component, which dominates among the Chulym Turks and Kets, the East Siberian component, which prevails among the Yakuts and Evenks, and the Far Eastern component, the frequency of which is maximum among the Nivkhs and Udeges. Analysis of the composition of IBD-blocks on autosomes shows the maximum genetic relationship of the Tuvans with the Southern Altaians, Khakas and Shors, who were formed during the settlement of the Turkic groups of populations on the territory of the Altai-Sayan region. A very diverse composition of the Tuvan gene pool is shown for various sublines of Y-chromosomal haplogroups, most of which show strong ethnic specificity. Phylogenetic analysis of individual Y-chromosome haplogroups demonstrates the maximum proximity of the gene pool of the Tuvans with the Altaians, Khakas and Shors. Differences in frequencies of Y-chromosome haplogroups between the Todzhans and Tuvans and a change in the frequencies of haplogroups from south to north associated with the East Asian component were found. The majority of the most frequent Y-chromosome haplogroups in the Tuvans demonstrate the founder effect, the formation age of which is fully consistent with the data on their ethnogenesis.